Parents' views on early marriage of girls in Bondowoso community - Hasan Assidiqi, Ali; Mujtahid; Sadiyah, Dini; Fajar Maulana, Hafidz (Jurnal Anifa: Studi Gender dan Anak, 2025)
Despite significant societal progress and increased access to education, early marriage, particularly among girl, remains prevalent in certain communities. This practice stands in contrast to existing regulations that mandate a minimum marriage age of 18 and 12 years of compulsory education, especially for parents who are already married. This study aims to explore parents’ perspectives on early marriage for their daughters and to identify the underlying causes. Employing a qualitative research method, data were collected through interviews and observations. The findings reveal two key points: (1) while most parents do not desire early marriage for their daughters and prefer that they continue their education and pursue employment, economic hardship often compels them to marry their daughters off in the hope of reducing the family’s financial burden. (2) Early marriage is driven by both internal and external factors, including environmental, social, economic, and cultural influences. Among these, limited economic resources and poor access to education, particularly at the junior high school level, emerge as the dominant causes. In such contexts, early marriage has become normalized as a cultural practice.